Incidental findings related to genes associated to HAE-nC1INH: how to proceed? - Germenis, Anastasios E.; Sanoudou, Despina (Frontiers in Immunology, 2025)
In contrast to hereditary angioedema (HAE) due to C1-inhibitor deficiency, the detection of pathogenic variants in genes linked to HAE with normal C1 inhibitor levels (HAE-nC1INH) is required for the diagnosis of the corresponding types of the disease. The mainstreaming of genomic technology and the increasing use of next generation sequencing have increased the possibility of an unintentional detection of HAE-nC1INH pathogenic variants and allowed the incidental finding of variants of uncertain significance (VUS) in the relevant genes. Apart from F12 and PLG pathogenic variants, the current level of evidence on the prevalence and penetrance of variants associated with HAE-nC1INH does not support the reporting of their incidental finding. On the other hand, although VUS should not be used in clinical decision-making, further consideration is warranted (a) for VUS found in exon 9 of the F12 gene after a diagnostic genetic analysis of individuals either with or without personal or family history of angioedema, and (b) for VUS found in any of the other genes linked to HAE-nC1INH, after genetic analysis performed in the context of differential diagnosis of angioedema cases. Given the complexity of interpreting, reporting and communicating incidental findings, a close partnership between patients, clinicians, laboratory geneticists and genetic counsellors is essential to optimize the management of these results.